A case report of xanthogranulomatous inflammation of a tubo-ovarian mass - Kamalanabane, Badmavathi; Ammulu, Srinivasan; Jayashree; Fathima, Shaheen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Although uncommon, xanthogranulomatous inflammation of the female reproductive system frequently manifests in the endometrium. There have only been a few documented incidences affecting the ovary. It may resemble ovarian cancer in its clinical presentation, radiological characteristics, and other aspects. Clinicians and pathologists should be aware of the importance of pre-diagnosing this inflammatory lesion in order to avoid misdiagnosis and drastic surgical treatment. This case report elaborates how a 60-year-old female patient with a tubo-ovarian tumor was suspected of having cancer based on clinic-radiological symptoms, but histological confirmed the ultimate diagnosis of xanthogranulomatous inflammation of an tubo ovarian mass.